Effects of tea and coffee on tooth discoloration - Kim, Soyeon; Son, Ji Eun; Larnani, Sri; Sim, Hye-Young; Yun, Pil-Young; Kim, Young-Jae; Park, Young-Seok (Italian Journal of Food Science, 2024)
Tooth discoloration because of dietary habits is a serious concern, particularly from tea and coffee consumption. This study investigated the effects of these beverages on tooth discoloration, focusing on their key chemical components. Bovine enamel specimens were immersed in green and black tea samples and Arabica and Robusta coffee samples for 1–72 h. High-performance liquid chromatography analyzed catechins, theaflavins, and chlorogenic acids, while spectrophotometry measured discoloration. Multiple regression analysis (significance at p < 0.05) revealed that all beverages caused significant tooth discoloration, with black tea showing the most pronounced effect because of its theaflavin content.